Chatter suppression in end milling of Titanium alloy Ti6Al4V applying permanent magnet clamped adjacent to the workpiece - Amin, A. K. M. Nurul; Azhari, A.; Mahmud, Md. Asif (IIUM Press, 2011)
Chatter is an unwanted but sometimes unavoidable phenomenon in machining. The term defines the self-excited violent relative dynamic motion between the cutting tool and workpiece. Nakagawa et al. [1] stated it is meant as a problem has emerged during the endmilling of hardened steels. Campa et al. [2] described chatter as a dynamic problem at high removal rate conditions. Chatter is undesirable due to its adverse effects on the product quality, operation cost, machining accuracy, tool life, machine-tool bearings, and machinetool life. It is also responsible for reducing output because if chatter cannot be controlled, then metal removal rates have to be lowered to eliminate chatter. Hence chatter must be avoided to improve the dimensional accuracy and surface quality of the product [3]. A system having self-induced vibrations can be said to have a negative damping [4]. In addition, Quintana et al. [5] specified that chatter can be obviously predicted from the loud noise and the poor surface integrity due to the chatter mark.The chatter phenomenon actually can be suppressed by some of methods. Nakagawa [1] showed that an end-mill with different helix angles could prevent generative chatter vibration at lower cutting speeds and was also effective in suppressing chatter vibration at higher cutting speeds. Chatter conventionally, is determined using Fast Fourier Transformation (FFT), determining whether received voice signals from a sensor are high frequency signals. The analytical and experimental identification of the chatter frequencies in milling processes and the frequency diagram are attached to the stability charts of the mechanical models. Kim et al. [6] also showed the chatter prediction method in this study. With the advancement of a chatter monitoring, the conventional FFT (Fast Fourier Transform) method was generally used. But it needs huge number of data for reliable monitoring of end-milling force. In this chapter a new method of chatter control is introduced for suppression of chatter during end milling of titanium alloy Ti6Al4V. The magnet is clamped together with the workpiece using the machine vise. Since titanium alloys are non-magnetic in nature this method could be employed. However, the strength of the magnetic field can’t be maintained uniform at all machining locations on the workpiece.